Enhancing the Competitiveness of Islamic Elementary Schools through Service Differentiation and School Image Modernization - Maya Diaz Restarie; R Madhakomala R Madhakomala; Siti Zulaikha; Syafa’at Ariful Huda (Journal of Educational Sciences, 2026)
This study aims to analyze the direction and trends of research on service differentiation and school image as a competitiveness strategy for Islamic elementary schools in the modern education era. The study employed a Systematic Literature Review (SLR) using the PRISMA method, drawing data from Scopus and Google Scholar within the 2020–2025 range. A total of 98 articles were identified based on relevant keywords. After a systematic selection process and screening using inclusion–exclusion criteria, 29 articles were considered eligible for deeper analysis. The findings indicate that recent research trends focus on the synergy between service quality, school image, and digital transformation as the main pillars of competitiveness among Islamic educational institutions. Cluster analysis revealed four dominant themes: school image and reputation, service quality and competitive advantage, digital branding strategies, and the local context of Islamic schools in Indonesia. This study demonstrates that the success of Islamic elementary schools in the modern era is determined not only by religious values but also by institutional capability in managing services, building digital reputation, and developing public trust strategically.